2022
DOI: 10.1002/aur.2715
|View full text |Cite
|
Sign up to set email alerts
|

Elevated symptoms of executive dysfunction predict lower adaptive functioning in 3‐year‐olds with autism spectrum disorder

Abstract: Executive functioning (EF) deficits co-occur frequently with autism spectrum disorder (ASD) and have a long-term detrimental impact on quality of life of children and their families. Timely identification of risk for EF vulnerabilities may hasten access to early intervention and alleviate their long-term consequences. This study examines (1) if EF deficits are elevated in toddlers with ASD compared to nonautistic siblings of children with ASD, typically developing (TYP) toddlers, and toddlers with atypical dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…These interventions would most likely be most successful in preventing future EP for children with fewer social autism symptoms. However, given the executive functioning impairments common in ASD (Powell et al, 2022) and executive functioning's association with multiple other domains of life such as school readiness (Shaul & Schwartz, 2014), language skills (Gooch et al, 2016), and adaptive behavior (Clark et al, 2002), executive functioning interventions would most likely be beneficial for children at all levels of autism symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These interventions would most likely be most successful in preventing future EP for children with fewer social autism symptoms. However, given the executive functioning impairments common in ASD (Powell et al, 2022) and executive functioning's association with multiple other domains of life such as school readiness (Shaul & Schwartz, 2014), language skills (Gooch et al, 2016), and adaptive behavior (Clark et al, 2002), executive functioning interventions would most likely be beneficial for children at all levels of autism symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Facets of executive functioning emerge in the first years of life and continue to develop throughout childhood and adolescence, with significant development occurring in the preschool years (Best & Miller, 2010). Children with ASD often show delayed executive functioning development (Rosenthal et al, 2013) and greater executive functioning impairment compared to their typically developing peers (O'Hearn et al, 2008; Smithson et al, 2013), with differences appearing as early as age three (Powell et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…According to McClain, the most affected EF domain in all these groups was working memory. Studies have shown that lower EF performance is related with lower adaptive social, communication, and daily living skills, even when controlling for autism severity (Powell et al, 2022). Thus, regardless of the autism severity level, low EF have a negative effect on everyday functioning.…”
Section: Introductionmentioning
confidence: 99%